HLA-DR allele reading register shifting is associated with immunity induced by SERA peptide analogues (2008)
SERA protein is a leading candidate molecule to be included in an antimalarial vaccine. Conserved high activity binding peptides (HABP) binding to red blood cells (RBC) have been identified in this protein. One of them (6762) localising in the 18-kDa C-terminal fragment was used to induce protective immunity with negative result. Critical RBC binding residues (assessed by glycine-analogue scanning) were replaced by others having the same mass, volume and surface but different polarity, rendering some of them immunogenic as assessed by antibody production against the parasite or its proteins and protection-inducing against challenge with a highly infectious Aotus monkey-adapted Plasmodium falciparum strain. A shift in binding to purified HLA-DR allelic molecules from the same haplotype and in their reading register was found, suggesting that modified molecules had adopted a different 1H NMR 3D structure allowing a better fit into the MHCII–pept-TCR complex, thereby representing a new mechanism for inducing immune protection.